Urgensi Penerapan Rupiah Digital (Central Bank Digital Currency) Sebagai Solusi Modern Dalam Permasalahan Sistem Pembayaran di Indonesia - Eris Manurung (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2025)
The implementation of the Digital Rupiah (Central Bank Digital Currency/CBDC) in Indonesia is a modern solution to improve the payment system which is hampered by limited infrastructure, low financial inclusiveness, security threats and high transaction costs. The type of research used in this writing is the Literature Study Method. Its function is to analyze the potential of the Digital Rupiah (CBDC) as Digital currency in increasing transaction efficiency, financial inclusiveness, monetary stability and improving payment system problems. From the analysis results, Digital Rupiah is able to be a solution to payment system problems because it can speed up transactions, reduce costs, and facilitate access to financial services for the public. However, for its implementation in Indonesia the Digital Rupiah still has challenges, namely the required technological infrastructure, data privacy, security, regulations and laws that still need to be overcome and developed. Collaboration between regulators, the Government, the private sector and other stakeholders is needed to design an effective implementation of the Digital Rupiah. This research provides an in-depth understanding of the urgency and implications of implementing the Digital Rupiah in the Indonesian context.